The Relationship Between Medication Compliance And The Incidence Of Hypertension Crisis In RSUD. Haji Makassar - I Kade Wijaya; Risna; Muh. Zukri Malik; Musmulyadi; Muh Taslim (Comprehensive Health Care, 2023)
A hypertension crisis is an acute complication characterized by a severe increase in blood pressure, generally occurring ≥ 180/120 mmHg. Risk factors for hypertension generally occur due to a history of disease in the family, and age factors as factors that cannot be modified. An unhealthy lifestyle, including consuming alcohol, uncontrolled hypertension, or compliance to taking antihypertension drugs, is a modifiable factor but is often the cause of chronic hypertension to lead to a hypertension crisis. The purpose of this study is to determine the relationship between medication compliance to the incidence of hypertension crisis in hospitals. Makassar Hajj. This study used a cross-sectional research design with a total sampling technique of 34 respondents. This research was carried out in the treatment room of RSUD Haji Makassar. From the results of the study, it can be concluded that compliance to taking medication is associated with the incidence of emergency hypertension with a value of p = 0.008, OR = 112; the more obedient to taking antihypertension drugs, the less likely people with hypertension are to experience hypertension emergencies.